Exact Kohn-Sham scheme based on perturbation theory - Görling, Andreas; Levy, Mel (Physical Review A, 1994)
An exact formal Kohn-Sham scheme is derived with the help of perturbation theory. Through the introduction of a basis set this Kohn-Sham scheme can be used to perform, in principle, exact Kohn-Sham calculations. As a demonstration, only zeroth- and first-order terms in the underlying perturbation theory are considered. As a result an exact basis set exchange-only method is obtained. The presented perturbation theory expansions of the exchange-correlation energy and potential may serve as a starting point for the development of new approximate exchange-correlation functionals based on Kohn-Sham orbitals and eigenvalues and may be used to check conventional exchange-correlation functionals. The formal structures of the ab initio and the introduced density-functional treatment of electronic systems are compared. © 1994 The American Physical Society.